2022
DOI: 10.1021/acs.energyfuels.2c01349
|View full text |Cite
|
Sign up to set email alerts
|

Light-Driven Hydrogen Production from Steam Methane Reforming via Bimetallic PdNi Catalysts Derived from Layered Double Hydroxide Nanosheets

Abstract: Steam methane reforming is one of the primary industrial hydrogen sources but depends upon high temperatures to activate the inert C−H bonds in methane, motivating novel methods to achieve more sustainable methane activation and hydrogen production. Here, we prepared a PdNi bimetallic catalyst derived from layered double hydroxides for light-driven steam methane reforming, achieving a hydrogen production rate of 82.9 mmol g −1 h −1 at 300 °C under xenon lamp illumination. Outdoor condensed sunlight irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 59 publications
(76 reference statements)
0
28
0
Order By: Relevance
“…In the review by Xiong et al, the advancements in semiconductor-based photocatalytic CH 4 conversion were discussed and the perspectives on co-catalysts for promoting the photoactivity were proposed . Zhang’s group presented a PdNi bimetallic catalyst derived from layered double hydroxide for light-driven steam methane reforming . Dai and Fu investigated the effects on three different shapes of the CeO 2 surface on photothermal CO 2 methanation .…”
Section: Decarbonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the review by Xiong et al, the advancements in semiconductor-based photocatalytic CH 4 conversion were discussed and the perspectives on co-catalysts for promoting the photoactivity were proposed . Zhang’s group presented a PdNi bimetallic catalyst derived from layered double hydroxide for light-driven steam methane reforming . Dai and Fu investigated the effects on three different shapes of the CeO 2 surface on photothermal CO 2 methanation .…”
Section: Decarbonizationmentioning
confidence: 99%
“…53 Zhang's group presented a PdNi bimetallic catalyst derived from layered double hydroxide for light-driven steam methane reforming. 54 Dai and Fu investigated the effects on three different shapes of the CeO 2 surface on photothermal CO 2 methanation. 55 It was found that the introduction of a N dopant resulted in the transformation of the TiO 2 phase from anatase to rutile, thus leading to improved CH 4 selectivity.…”
Section: ■ Photooxidationmentioning
confidence: 99%
“…Photocatalysis, employing inexhaustible solar energy instead of thermal energy, provides an attractive alternative route to sustainable CH 4 conversion under ambient reaction conditions [11][12][13][14][15]. Among various methane conversion schemes, nonoxidative coupling of CH 4 to ethylene (C 2 H 4 ) along with simultaneous production of H 2 is a preferable pathway, as C 2 H 4 is the high value-added key chemical feedstock, while H 2 is an important clean energy carrier.…”
Section: Introductionmentioning
confidence: 99%
“…However, this process requires high temperatures (> 700 °C), resulting in high energy consumption. [1] An alternative method for hydrogen production, namely, photocatalytic water splitting, is a promising method because of the utilization of inexhaustible solar energy sources and a mild, clean, and pollution-free reaction process. [2] However, low photocatalytic efficiency remains the main factor restricting its industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, methane steam reforming with high conversion efficiency is widely used for industrial hydrogen production. However, this process requires high temperatures (>700 °C), resulting in high energy consumption [1] . An alternative method for hydrogen production, namely, photocatalytic water splitting, is a promising method because of the utilization of inexhaustible solar energy sources and a mild, clean, and pollution‐free reaction process [2] .…”
Section: Introductionmentioning
confidence: 99%